Crosstalk between immune checkpoint and DNA damage response inhibitors for radiosensitization of tumors - Classen, Sandra; Petersen, Cordula; Borgmann, Kerstin (Strahlentherapie und Onkologie, 2023)
Purpose This review article is intended to provide a perspective overview of potential strategies to overcome radiation resistance of tumors through the combined use of immune checkpoint and DNA repair inhibitors. Methods A literature search was conducted in PubMed using the terms (“DNA repair* and DNA damage response* and intracellular immune response* and immune checkpoint inhibition* and radio*”) until January 31, 2023. Articles were manually selected based on their relevance to the topics analyzed. Results Modern radiotherapy offers a wide range of options for tumor treatment. Radiation-resistant subpopulations of the tumor pose a particular challenge for complete cure. This is due to the enhanced activation of molecular defense mechanisms that prevent cell death because of DNA damage. Novel approaches to enhance tumor cure are provided by immune checkpoint inhibitors, but their effectiveness, especially in tumors without increased mutational burden, also remains limited. Combining inhibitors of both immune checkpoints and DNA damage response with radiation may be an attractive option to augment existing therapies and is the subject of the data summarized here. Conclusion The combination of tested inhibitors of DNA damage and immune responses in preclinical models opens additional attractive options for the radiosensitization of tumors and represents a promising application for future therapeutic approaches.